JOKOWI DAN PRABOWO, MENYELISIK ISU “SONTOLOYO” DAN “TAMPANG BOYOLALI” PADA KOMPAS.COM (Fakultas Dakwah dan Komunikasi, 2020)
This research is aimed to know on how to overview the content of the news and get across the trend of kompas.com related to the content news of the issue of Sontoloyo and Tampang Boyolali. The results identifies that based on the resource category and the main issue of Sontoloyo and Tampang Boyolali which presented by kompas.com obtained various results. For the issue of Sontoloyo, the content is more likely to be obtained from experts/intellectuals, while for the issue of Tampang Boyolali obtained from BPN or Badan Pemenangan Nasional. The most widely reported issue by kompas.com is a Tampang Boyolali issue consists of 42 news items with a percentage of 72.4%. In terms of comments on the issue of Sontoloyo and Tampang Boyolali on Kompas.com, indicates that both issues get negative results in the news, but the issue of Tampang Boyolali obtains more prominent result of 18 news items with a percentage of 41.8%, compared to Sontoloyo issues as many as 5 news items with a percentage of 33.3%.